The SABRTooth feasibility trial protocol: a study to determine the feasibility and acceptability of conducting a phase III randomised controlled trial comparing stereotactic ablative radiotherapy (SABR) with surgery in patients with peripheral stage I non-small cell lung cancer (NSCLC) considered to be at higher risk of complications from surgical resection. Issue 1 (December 2016) - Snee, M.; McParland, L.; Collinson, F.; Lowe, C.; Striha, A.; Baldwin, D.; Naidu, B.; Sebag-Montefiore, D.; Gregory, W.; Bestall, J.; Hewison, J.; Hinsley, S.; et al.
Abstract Background Stage I non-small cell lung cancer (NSCLC) is potentially curable, and surgery is considered to be the standard of care for patients with good performance status and minimal co-morbidity. However, a significant proportion of patients with stage I NSCLC have a poorer performance status and significant medical co-morbidity that make them at higher risk of morbidity and mortality from surgery. Stereotactic ablative radiotherapy (SABR), which uses modern radiotherapeutic techniques to deliver large doses of radiation, has shown superiority over conventional radiotherapy in terms of local control and toxicity and is a standard of care for patients with stage I NSCLC who are at too high risk for surgery. However, it is not known whether surgery or SABR is the most effective in patients with stage I NSCLC who are suitable for surgery but are less fit and at higher risk surgical complications. Previous randomised studies have failed to recruit in this setting, and therefore, a feasibility study is required to see whether a full randomised control trial would be possible. Methods/design SABRTooth is a UK-based, multi-centre, open-label, two-group individually (1:1) randomised controlled feasibility study in patients with peripheral stage I NSCLC considered to be at higher risk from surgical resection. The study will assess the feasibility of conducting a definitive large-scale phase III trial. The primary objective is to assess recruitment rates to provide evidence that, when scaled up, recruitment to a large phase III trial would be possible; the target recruitment being 54 patients in total, over a 21-month period. There are multiple secondary and exploratory objectives designed to explore the optimum recruitment and data collection strategies to help optimise the design of a future phase III trial. Discussion To know whether SABR is a better, equivalent or inferior alternative to surgery for higher risk patients is a key question in lung cancer. Other studies comparing SABR to surgery have closed early due to poor recruitment, and therefore, the SABRTooth feasibility study has been designed around the UK National Health Service (NHS) cancer pathway incorporating many design features in order to maximise recruitment for a future definitive phase III trial. Trial registration controlled-trials.comISRCTN13029788